The London Model: forecasting fog at 333 m resolution. (2nd October 2015) - Boutle, I. A.; Finnenkoetter, A.; Lock, A. P.; Wells, H.
Abstract : A very high resolution numerical weather prediction model is nested inside the Met Office's main United Kingdom forecast model to investigate whether further enhancements to resolution provide any benefit for fog forecasting. The London Model shows similar performance to its lower resolution equivalent at short lead times, but improved performance at longer lead times and an improved frequency bias of forecast fog events. Differences in the model cloud parametrization are the key reason for the differing behaviour, leading to systematically less cloud, colder night time minimum temperatures and therefore more fog in the London Model. Benefit of the enhanced resolution is also found, via an improved representation of how orographic variability enhances turbulence in the stable boundary layer.